2022
DOI: 10.1097/opx.0000000000001973
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Thickness Profiles and Associated Factors in Myopic Children

Abstract: SIGNIFICANCEThis study addresses the lack of choroidal thickness (ChT) profile information available in European children and provides a baseline for further evaluation of longitudinal changes in ChT profiles in myopic children as a potential biomarker for myopia treatment and identifying children at risk of myopic progression.PURPOSEThis study aimed to investigate ChT profiles and associated factors in myopic children.METHODSBaseline data of 250 myopic children aged 6 to 16 years in the Myopia Outcome Study o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…This study recruited myopic participants (aged 6-16 years and 4-12 years for the cyclopentolate and tropicamide groups, respectively) involved in two clinical trials exploring the efficacy and safety of low-dose (0.01% or 0.02%) atropine at the Centre for Eye Research Ireland, as previously described. 20,21 The studies were approved by the Research Ethics Committees at the Mater Misericordiae University Hospital, Ireland, Tallaght University Hospital, Ireland and Technological University Dublin, Ireland and adhered to the tenets of the Declaration of Helsinki. Participants and their parents provided written informed assent and consent, respectively, prior to enrolling in the studies.…”
Section: Study Participantsmentioning
confidence: 99%
“…This study recruited myopic participants (aged 6-16 years and 4-12 years for the cyclopentolate and tropicamide groups, respectively) involved in two clinical trials exploring the efficacy and safety of low-dose (0.01% or 0.02%) atropine at the Centre for Eye Research Ireland, as previously described. 20,21 The studies were approved by the Research Ethics Committees at the Mater Misericordiae University Hospital, Ireland, Tallaght University Hospital, Ireland and Technological University Dublin, Ireland and adhered to the tenets of the Declaration of Helsinki. Participants and their parents provided written informed assent and consent, respectively, prior to enrolling in the studies.…”
Section: Study Participantsmentioning
confidence: 99%
“…In particular, a multiethnic study conducted among Asian populations, including Malay, Chinese, and Indian individuals, has identified significant differences in choroidal thickness among different ethnic groups, even after adjusting for factors such as age, gender, and axial length [ 17 ]. Additionally, a study found that the choroid is thinner in the para and perifoveal regions of Asian children compared to European children [ 18 ]. This suggests that there may be underlying genetic factors contributing to the observed differences in choroidal thickness.…”
Section: Introductionmentioning
confidence: 99%